Perceptions of effectiveness of celebrity endorsed advertisements among Egyptian consumers - Azab, Marwa Diaa El Din (AUC Knowledge Fountain, 2011)
The main purpose of this study is to investigate consumer attitudes regarding celebrity endorsement in different types of media in Egypt, and presents guidance to advertising specialists and creators to enhance the value of celebrity-based advertising. The study was based on an empirical research approach, which used a convenience sample of 355 respondents, drawn from different age groups, educational level, income level and residential areas. The data was analyzed by a variety of statistical techniques, such as Descriptive analysis, Frequency analysis, t-Test, and ANOVA. The main findings revealed that Egyptians respondents were in general interested in celebrity endorsement advertisements, as the majority of them admitted its attractiveness; however, they did not find it enough convincing in terms of purchasing behavior. The study recommended reconsidering the use and choice of celebrities in advertising within the context of the Egyptian culture. The study also recommends further research to investigate this issue in more depth in Egypt. The study suggested some other recommendations in light of the findings.